Perubahan Strategi Perjuangan Era Pergerakan Nasional: Dari Strategi Non-Kooperatif ke Kooperatif - Rusmala Dewi Kabubu; La Malihu (Universitas Negeri Makassar, 2026)
This article examines the transformation of struggle strategies in the Indonesian national movement from non-cooperative to cooperative approaches during the 1930s. It argues that this shift should be understood not merely as a tactical adjustment but as a transformation of collective consciousness shaped by the colonial socio-historical context, while also assessing its effectiveness in the independence struggle. The study employs the historical method, encompassing heuristic inquiry, source criticism, interpretation, and historiography, drawing on relevant scholarly literature. The analysis is informed by Karl Mannheim’s sociology of knowledge, particularly the concepts of utopia, ideology, and situational knowledge. The findings demonstrate that the non-cooperative strategy embodied a transformative utopian orientation, whereas structural pressure, most notably political repression and the global economic depression, prompted a reconfiguration of the elites’ situational knowledge. This shift gave rise to cooperative strategies as adaptive forms of ideology that operated within colonial structures without relinquishing the goal of independence. The transition thus reflects a dialectical relationship between utopia and ideology within the evolving dynamics of the national movement. This study contributes by conceptualizing strategic change as a transformation of collective consciousness rather than a purely tactical response, thereby advancing theoretically grounded historiography of the Indonesian national movement.